Bangers and cash: Baiting efficiency in a heterogeneous population - Naomi Indigo; James Smith; Jonathan K. Webb; Ben L. Phillips (Wildlife Society Bulletin)
ABSTRACT Uptake of baits is a key variable in management actions aimed at the vaccination, training, or control of many vertebrate species. Increasingly, however, it is apparent that individuals of the target species vary in their likelihood of taking baits. To optimize a baiting program, knowledge on the rate of bait uptake, how this rate changes with bait availability, and the proportion of the target population that will take a bait is required. The invasive cane toad (Rhinella marina) in Australia is a major threat to northern quolls (Dasyurus hallucatus), which are poisoned when they attack this novel toxic prey item. Conditioned‐taste‐aversion baits (cane toad sausages) can be delivered in the field to train northern quolls to avoid toads. We conducted a large‐scale field trial among 11 sites across one large property in Western Australia from 19–26 July 2017. We used camera traps and statistical modelling to estimate the proportion of baitable animals in the population, their encounter rate with baits, and survival rate of baits in the environment. Population estimates varied at each site from 2.5 to 16.8 quolls per site, resulting in a range among sites of 0.7–4.6 baits available/individual. Approximately 64% of individual quolls were bait‐susceptible. Both encounter rate and bait survival were low, resulting in our baiting regime treating <30% of the bait‐susceptible population. Using our model parameters, we estimate that we would need to increase our bait density 6‐fold to treat all bait‐susceptible individuals in the population. Without accounting for heterogeneity in bait‐susceptibility, our model would suggest we would need a 10‐fold increase in bait density. Thus, accounting for heterogeneity provides a more efficient baiting design. Data and models such as ours provide wildlife managers with information critical to informed decision‐making and are fundamental to estimate the cost‐efficiency of any baiting campaign. © 2019 The Wildlife Society.